REALITAS MASYARAKAT ADAT DI INDONESIA: SEBUAH REFLEKSI - Haba, John (P2KK LIPI, 2010)
Adat Community around the globe particularly in Indonesia is facing a massive problem. This phenomenon refers to two cardinal issues namely: the willingness of the government to recogize their rights and existence, and how to maximizing their participation in national development programs. This paper deals with certain issues such as definition and concepts being debated, inconsistency to link between local history, identity socio-cultural and economic rights of the adat community. In this stage, the first party responsible for empowering the adat community is the government, however there is an immense disparity between ideal plan to empower them, and systemic deteriorating of the peoples’ life condition and all of their right. Implying some definitions and categories, this paper underlines as well as the actual life condition of adat community currently, that is not merely impacted on external factors but also from internal factors. This paper ends with six conclusions to emphazise ways for coping with current crisis of the adat community in Indonesia. Keywords: adat community, current realities and reflection.